Neutrophil-to-Lymphocyte Ratio in Adult Patients with Anemia: A Hospital-Based Cross-Sectional Study - Manandhar, Nilu; Bhattarai, Kushal; Bhandari, Krishant (Journal of Karnali Academy of Health Sciences, 2023)
Background: Neutrophil-to-lymphocyte ratio, a well-defined marker of immunity, is raised in many conditions which are characterized by abnormal inflammatory and immunological responses. Anemia of chronic disease, the most prevalent type in hospitalized patients, is a dominant clinical picture in protracted stimulation of immunity. This study aimed to assess the neutrophil-to-lymphocyte ratio in adult participants with anemia and to compare of the ratio with non-anemic participants.Methods: In a cross-sectional study conducted in the Department of Clinical Physiology of Karnali Academy of Health Sciences, Teaching Hospital, Jumla, Karnali Province, Nepal, in the months of August, 2023, data on clinico-demographic variables were retrieved from the laboratory information system of hospital records of February–March, 2023. From the hematological parameters retrieved, the status of anemia and the neutrophil-tolymphocyte ratio were calculated.Results: After scrutiny of the laboratory records of 1421 adult patients, with 69.7% (N=990) female, the prevalence of anemia was 12.4% (N=176) and the median neutrophil-to-lymphocyte ratio was 2.21 (IQR: 1.41–3.75). The median neutrophil-to-lymphocyte ratio was significantly greater in the anemic participants among the overall (p